Studies on [3]pseudorotaxane formation from a bis-azacrown derivative as host and imidazolium ion-derivatives as guest - Mandal, Amal Kumar; Suresh, Moorthy; Das, Amitava (Organic & Biomolecular Chemistry, 2011)
A new host molecule, having two azacrown derivatives bridged by luminescent naphthalene diimide functionality, is found to form a [3]pseudorotaxane derivative with imidazolim ion-based guest molecules in non-polar solvents through hydrogen-bonded adduct formation. Depending upon the length of the covalent linker that links the imidazolium ion and the luminescent naphthalene fragment in the guests, the [3]pseudorotaxane adducts adopt different conformation or orientation with varying π–π/donor–acceptor interaction. The mechanism for the naphthalene-based luminescence quenching by NDI fragment on adduct formation was found to be a combination of static, as well as dynamic with static quenching as the dominant one.